2016
DOI: 10.1088/2050-6120/4/2/022001
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence polarization assays in high-throughput screening and drug discovery: a review

Abstract: The sensitivity of Fluorescence Polarization (FP) and Fluorescence Anisotropy (FA) to molecular weight changes has enabled the interrogation of diverse biological mechanisms, ranging from molecular interactions to enzymatic activity. Assays based on FP/FA technology have been widely utilized in high-throughput screening (HTS) and drug discovery due to the homogenous format, robust performance and relative insensitivity to some types of interferences, such as inner filter effects. Advancements in assay design, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
148
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(151 citation statements)
references
References 109 publications
0
148
0
3
Order By: Relevance
“…The accurate determination of thermodynamic parameters of molecular interactions is performed by fast, but superficial high-throughput (HTP) methods. In the literature several HTP approaches are applied such as co-immunoprecipitation [2], yeast two hybrid and spot assays [3], pull-down assay [4], holdup assay [5] and direct fluorescence polarization/anisotropy [6]. In direct fluorescence polarization (FP) experiments, a fluorescent probe (usually a labeled peptide) is titrated with a globular partner.…”
Section: Introductionmentioning
confidence: 99%
“…The accurate determination of thermodynamic parameters of molecular interactions is performed by fast, but superficial high-throughput (HTP) methods. In the literature several HTP approaches are applied such as co-immunoprecipitation [2], yeast two hybrid and spot assays [3], pull-down assay [4], holdup assay [5] and direct fluorescence polarization/anisotropy [6]. In direct fluorescence polarization (FP) experiments, a fluorescent probe (usually a labeled peptide) is titrated with a globular partner.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that BI is an easily implementable local strategy, within the reach of current experimental techniques, that performs quasioptimally. The identification of quantum change points demonstrated in our experiment might be applicable in many practical situations, such as identifying domain walls in condensed matter systems [34] and detecting the changes of fluorescence polarization in some biological processes [35]. Our work can also be extended to high dimensional quantum states, mixed states, and multiple change points.…”
mentioning
confidence: 73%
“…In DSF, changes in protein stability due to small‐molecule binding are quantified by assessing thermal shifts in the presence of a dye, such as SYPROÂź Orange, which becomes more fluorescent when bound to unfolded proteins. Applications of both FP and DSF in high‐throughput screening (HTS) and drug development are well known and have been thoroughly reviewed …”
Section: Figurementioning
confidence: 99%